Integrating Prophetic Counseling Methods into Modern School-Based Mental Health Programs: A Case Study in Islamic Boarding Schools - Masrukhin, Akhmad Rudi; Hakim, Faisol; Ashari, Beni; Zainuri, Zainuri; Nita, Perabu (Yayasan Minang Darussalam, 2025)
This study explores the integration of Prophetic counseling methods into contemporary school-based mental health programs, with a particular focus on Islamic boarding schools (pesantren) in Indonesia. Amid increasing concerns over student mental health, there is a growing need for culturally and spiritually responsive counseling approaches. Prophetic counseling, derived from the teachings and practices of the Prophet Muhammad (peace be upon him), emphasizes empathy, active listening, moral guidance, and emotional regulation within a spiritual framework. This qualitative case study employed interviews, observations, and document analysis to examine how Islamic boarding schools incorporate these Prophetic principles into their student support systems. Findings indicate that combining modern psychological strategies with Prophetic values fosters a holistic and contextually appropriate mental health model, enhancing students' emotional well-being, resilience, and moral development. The study concludes that the synergy between Islamic ethical traditions and modern mental health practices can enrich school counseling frameworks and offers a model that can be adapted in other faith-based educational settings.